ANALISIS EFEKTIVITAS APLIKASI MONGGO LAPOR PADA PENINGKATAN PELAYANAN PUBLIK DI KOTA MAGELANG - Pertiwi, Putri Ika (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
In order to realize its commitment to becoming a smart city, Magelang City has developed various digital innovations to accelerate the government's response to the needs of its citizens. One of the featured applications developed is